Renal cell carcinoma accompanied by aldosterone-secreting contralateral adrenal metastasis: a case report - Modar Doyya; Ghina Alloush; Mazen Alloush (Journal of Medical Case Reports)
Abstract Background Kidney cancer is a highly prevalent malignancy, consistently ranking among the top ten cancers affecting both men and women, and its mortality has been increasing globally. Renal cell carcinoma is the most common type and has a tendency to metastasize, with a predilection for spreading to other organs. While the adrenal gland is located adjacent to the kidney, metastasis of renal cell carcinoma to the adrenal gland is considered rare compared with other sites such as the lungs, liver, and bones. In addition, the occurrence of metastasis to the contralateral adrenal gland is an exceedingly rare phenomenon. Case presentation A 57-year-old Arabic female patient presented with intermittent hematuria over a period of several months. The patient’s medical and surgical history revealed no significant findings. Laboratory tests revealed normal results, with the exception of elevated aldosterone levels and a high aldosterone renin ratio, despite a normal blood pressure reading. Further investigations revealed the coexistence of renal cell carcinoma and adrenal adenoma on the left side, along with adrenal mass on the right side, which confirmed its metastatic nature after resection and pathological study. As a result, a left nephrectomy and right adrenalectomy were subsequently conducted. Postsurgery, the aldosterone level normalized, confirming the secretory function of the metastasized renal carcinoma in the right adrenal gland. Conclusion The secretion of aldosterone from an adrenal metastasis arising from renal cell carcinoma is a rare phenomenon that healthcare providers should bear in mind during differential diagnosis. It is imperative to conduct thorough investigations and extended research to understand the potential complications associated with this unique presentation.